HUBUNGAN ANTARA MOTIVASI BELAJAR DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS 4 SDN 01 SUNGAI APIT - Destinur; Siti Quratul Ain (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study was to determine the relationship between learningmotivation and mathematics learning outcomes of grade 4 students of SDN 01Sungai Apit. This study uses a quantitative approach method. The data collectiontechnique in this study used a questionnaire. In this study, researchers took asample of 22 students from grade 4. Data were collected through interviews,questionnaires, and documentation. The results of the study indicate that there is arelationship between learning motivation and mathematics learning outcomes ofgrade 4 students of SDN 01 Sungai Apit. This is indicated by Sig (2-tailed)obtained a value of 0.000 <0.05, meaning that the relationship between the twovariables has a good correlation at the 0.05 level with a high category. r at asignificance level of 5% is 0.422 while rxy = 0.995 so that (0.0995> 0.422) isobtained and is included in the high category.